ASSOCIATION BETWEEN SLEEP QUALITY AND ANXIETY AMONG HIGH SCHOOL STUDENTS: A CROSS-SECTIONAL STUDY (Tạp chí Y học Cộng đồng, 2026)
Objective: To examine the association between sleep quality and anxiety levels among high school students.Subjects and Methods: The cross-sectional descriptive study was conducted among students aged 15 to 17 years from Hoa Vang High School who met the eligibility criteria. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while  generalized anxiety levels were measured using the Generalized Anxiety Disorder-7 (GAD-7) scale.Results: To determine the relationship between sleep quality and anxiety, a total of 737 high school students were surveyed (62.7% female; mean age 15.7 ± 0.87 years). The mean PSQI score was 5.9 ± 3.4, indicating relatively poor sleep quality, with female students reporting significantly poorer sleep than males (p < 0.001). Anxiety levels were also higher in females (mean GAD-7 score: 8.3 ± 4.6 vs. 5.8 ± 4.3 in males; p < 0.001). Additionally, 31.2% of students reported going to bed after midnight. Correlation analysis revealed a moderately strong, statistically significant positive association between sleep quality (PSQI) and anxiety (r = 0.543; p < 0.001), negative association between sleep duration per day and general anxiety (r=0.276, p
Keywords: Sleep quality, anxiety, high school students, Hoa Vang High School.